The Influence of Employee Engagement and Job Stress on Employee Performance at PT. Bank Syariah Indonesia Tbk. of Tangerang Cikupa Branch Office - Nurfadilah, Sri Dea; Sudinta, Heru (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This study aims to analyze the influence of employee engagement and work stress on employee performance at BSI KCP Tangerang Cikupa. Employee engagement is measured through three indicators, namely vigor, dedication, absorption, while work stress is assessed based on workload, leadership attitude, working hours, and conflict. Employee performance is measured through work quality, work quantity, task implementation, and responsibility. This study uses a quantitative approach with a survey method and data collection techniques through questionnaires distributed to all employees as a saturated sample. Data were analyzed using SPSS software version 30. The results showed that employee engagement has a positive and significant effect on employee performance, while work stress did not show a significant effect. Simultaneously, employee engagement and work stress together affect employee performance.